Indications and risk factors of blood transfusion in obstetrics and gynaecology - Laul, Poonam; Sampath, Akhila B.; Miglani, Urvashi; Jindal, Rikita; Yadav, Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Blood transfusion services are vital to maternal health because obstetric hemorrhage has been the foremost cause of maternal mortality in India. The purpose of the study is to study the indications and risk factors of transfusion of blood products in patients of obstetrics and gynaecology. The secondary objective is to study the type of early post blood transfusion reactions and percentage of patients referred from peripheral centre due to non-availability of blood transfusion centres Methods: A prospective cohort and observational study at Deen Dayal Upadhyay hospital, a New Delhi, India. Results: 21 to 30 years was the most common age group to receive blood transfusion. The 86.70 percent of the subjects requiring transfusion were of low socioeconomic status. 57.60 percent were not booked at any institute. The 60% of the patients were referred from elsewhere. Chronic anemia was most common associated haematological comorbidity (15.20%). The 85% received single component therapy transfusion. Amongst the patients receiving transfusion 11.2% had gynaecological disorder. The most common indication for transfusion was anemia in pregnancy. The 98.40% of the patients had no immediate or delayed blood transfusion reaction. Conclusions: Anemia in pregnancy is most common and important cause of transfusion of blood in antenatal population in Northern India. Anemia is a preventable condition. Operational blood storage systems at peripheral centres can reduce referral to tertiary care centre for blood transfusion. Transfusion of cross matched and screened blood components under supervision is extremely safe.